Gestión del archivo digital y su contribución en los procesos laborales del Gobierno Autónomo Descentralizado de Vinces - Gurumendy Valverde, Yelitza Jackeline (2019)
In this case study, information has been obtained on the subject: Management of the Digital Archive and its Contribution in Labor Processes, which used the interview technique using the closed and structured question survey tools focused on the management system Existing archival to achieve management aimed at officials and managers, one of the advantages, are oriented to the objective on them. In the same way, the changes they produce are specified on the problem, on the other hand they have knowledge that in remote times the file management of all the existing resources in the company in order to generate updated and truthful information, of the same way to meet the needs and stay in the market of the city of Vinces and sustainability and credibility of the company based on the factors generated by an archiving system, which is of quality and warmth, opting for the labor processes of the Vinces GAD. This case study is concluded by applying the general objective; establishing an archival management system to be used in a positive and affirmative manner for the officials and managers of said institution and in this way it is recommended that subordinates execute information requesting through a file management model to process the product required for the institution promoting job stability of the institution's employees